Can alfentanil or diltiazem prevent myocardial ischemia due to trachcal intubation? - BEKİROĞLU, GÜLNAZ NURAL (My University, 1999)
Objective: The aim of this study is to evaluate the efficacy of alfentanil and diltiazem to attenuate the ca rd io v a s c u la r responses to laryn g o sco p y and tracheal intubation and their effects on the occurrance of m yocardial ischem ia in patients with coronary artery disease. Methods: Tw enty eight patients A SA ll-lll, 40-80 years old, scheduled for elective abdom inal surgery were random ly assigned into three groups. A nesthesia was induced with 0.2 m g/kg etom idate and 1.5 m g/kg succinylcholine i.v. in all patients. In group I (n=10) 15 pg/kg alfentanil i.v. and in group II (n=10) 0.2 m g/kg diltiazem i.v. w ere adm inistered 2 m inutes before la ryn g o sco p y. In g roup III (n=8) (control) no m edication w as adm inistered. Systolic, diastolic, mean arterial pressure, heart rate, rate-pressure product and ST segm ent changes in Dll and V5 leads w ere recorded before and after induction at 1., 3., 5. m inutes of intubation. Results: M ean arterial pressure was significantly lower in the alfentanil and diltiazem group 1 m inute after intubation. T here w as no significant difference in heart rate betw een groups. R ate-pressure product was greater than 11000 in all patients of diltiazem and control groups and in 9 patients of alfentanil group. Conclusion: Although 0.2 m g/kg diltiazem and 15 p g /kg a lfe n ta n il i.v. a tte n u a te d the hyp e rte n sive response to tracheal intubation, they w ere found to be ineffective in decreasing the incidence of m yocardial ischem ia in coronary artery disease. K e y W o r d s : M yocardial ischem ia, alfentanil, d iltia ze m . T ra ch e a l intubation, hem odynam ic response.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Surgery Medicine Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Cerrahi; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Surgery; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; M yocardial ischem ia; alfentanil; d iltia ze m . T ra ch e a l intubation; hem odynam ic response